The effects of Elateriospermum tapos against obese maternal rat in mitigating obesity development among their adult female offspring - Bahari, Hasnah; Zainal Abidin, Azrina; Balan, Santhra Segaran; Perumal, Kokila Vani; Rosli, Nurain Syahirah; Ahamad Lotafi, Amalia Hazirah; Danabala, Sharmmila; Manimaran, Malarmugila; Shafie, Nurul Husna; Abdullah, Maizaton Atmadini; Jasni, Azmiza Syawani (Sage Publications, 2021)
Maternal obesity is a metabolic disorder described by chronic inflammation and dyslipidemia and influences non-communicable diseases in offspring. Elateriospermum tapos is a plant containing high alpha-linolenic acid with antiobesity effect. Objectives: This study was aim to investigate the effect of E. tapos supplementation in obese rat prior pregnancy on the female offspring's body weight, liver and kidney profile, and histological changes of heart, liver, kidney, and retroperitoneal white adipose tissue (RpWAT). Materials and Methods: Thirty female Sprague Dawley rats were used in this study. Six rats were assigned to dams normal diet group fed with standard chow diet. The remaining rats were fed with high-fat and cafeteria diet (HFCD) to generate obesity for 5 weeks. The obese rats were further divided into 4 groups; group1; Dams Negative Control (DNC, normal saline only), group 2; Dams Positive Control (DPC, Orlistat drug 200mg/kg), Dams Treatment 1 (DTX1, E. tapos seed 200 mg/kg) and Dams Treatment 2 (DTX2, E. tapos shell 200mg/kg) extracts for 6 weeks daily prior to mating. The weaning offspring were then designated into 6 groups according to their dam's group (n = 6/group). The offspring were culled at 12th week of age in order to have their blood sample and organs. Results: Adult offspring from DTX2 group showed a decrease in weight gain, alanine aminotransferase, and creatinine level compared to adult offspring from DNC. Histological examination showed that liver and RpWAT of offspring from DTX1 and DTX2 groups were comparable with normal diet group, indicating that the extracts were capable in reversing the high fat diet effect to the organ. Conclusion: E. tapos shell supplementation was effective in reducing the development of obesity with no harmful effect among adult female rat offspring.